ANALISIS UPAYA TANGKAP DAN POTENSI MAKSIMUM LESTARI IKAN TUNA MATA BESAR (Thunnus obesus) YANG DIDARATKAN DI PELABUHAN PERIKANAN SAMUDERA (PPS) KENDARI - Sulistiani Sulistiani; Andi Irwan Nur; Utama Kurnia Pangerang (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2024)
Research on bigeye tuna indicates the importance of analyzing the trend of fish-ing effort and the potential of Jestari bigeye tuna in the Banda Sea, in order to support sustainable fishing management. The purpose of this study was to determine the analy-sis of fishing effort and sustainable potential catch of bigeye tuna landed at PPS Kendari. The study was conducted in November December 2023 at the Kendari Ocean Fisheries Port (PPS). This study used a descriptive method and used secondary data. The results showed that the value of bigeye tuna fishing effort fluctuated from 2016-2022. In 2017 there was an increase with a value of 133 kg/ trip and in 2021 there was a decrease with a value of 32 kg/ trip. The results of the sustainable potential of bigeye tuna landed at PPS Kendari using the Fox model. The Fox model has an optimum effort value (Fusy) of 431 trips and a maximum catch value (Cu) of 42,174 kg/ year. The conclusion of this study is that the stock status of bigeye tuna in the Banda Sea is experiencing overfishing.